Factors associated with couple violence in pregnant women during the COVID-19 pandemic - Delgado-Herrera, Jackeline (2024)
Objective: To determine the factors associated with intimate partner violence in pregnant women during the Covid-19 pandemic at the San Luis Health Center, from January to December 2021. Materials and Methods: Observational, analytical case-control study. The population consisted of pregnant women attended in a primary care establishment, from which a sample was taken and distributed into a case group (133) and a control group (133). Partner violence was identified through the MINSA Violence Detection Sheet. The Chi-square test was used with a confidence level of 95%. In addition, crude (ORc) and adjusted (ORa) Odds Ratios were estimated, the latter using binary logistic regression. Results: The median age was 30 years; likewise, psychological violence prevailed (69.2%), followed by physical violence (50.4%) and sexual violence (9.8%). In the bivariate analysis, low educational level (ORc=2.07; p=0.026), violence prior to pregnancy (ORc=13.09; p=0.000), alcohol consumption by the partner (ORc=1.69; p=0.040) and a history of child violence (ORc=2.03; p=0.033) were factors that increased the probability of presenting intimate partner violence during pregnancy. However, after the multivariate analysis, only pre-pregnancy violence (ORa=13.98; p=0.000) was associated with intimate partner violence during the pandemic. Conclusion: Partner violence prior to pregnancy is the only factor associated with violence in pregnant women during the Covid-19 pandemic treated at C.S. San Luis.